1969
DOI: 10.1039/j19690001577
|View full text |Cite
|
Sign up to set email alerts
|

Formation of carbonylrhodium complexes in reactions with fluoroolefins

Abstract: A variety of fluoro-olefins react with RhCI(PPh,), and Rh, CI , L, to give the carbonyl complexes RhCI(CO)L, [L = Ph3P, (C6F&P, (C,F,),PhP, or (C6F5)Ph2P]. It is suggested that the carbon monoxide is formed by the action of small traces of water present in the reactions on fluoro-olefin complexes of the type RhCl(f1uoro-olefin) L, .The action of hydrogen chloride on RhCI(C,F,X) (PPh,), gives the fluoroethyl complexes RhCI,( CFX*CF,H) (PPh,),, (X = H, F, or CI) and it is proposed that this type of rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…CF activation promoted by addition of H 2 O : In an earlier study,16 we demonstrated that the trifluoroethylene‐bridged species analogous to 2 and 6 a undergoes facile fluoride ion loss in a reaction with water, giving [Ir 2 (CH 3 )(κ 1 ‐CHCF 2 )(CO) 2 (μ‐OH)(dppm) 2 ][OTf]. Carbon–fluorine bond activation by water is well documented,3f, 6d, 9a, 25 and Hughes and co‐workers have shown that the coordination of water can increase its acidity sufficiently to allow it to protonate an α‐fluorine atom,3f, 6d, 25 leading to its loss as HF. Consequently, we sought to determine whether water‐promoted CF activation could also occur for the C 2 F 4 ‐ and 1,1‐C 2 F 2 H 2 ‐bridged complexes ( 2 , 6 a or 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CF activation promoted by addition of H 2 O : In an earlier study,16 we demonstrated that the trifluoroethylene‐bridged species analogous to 2 and 6 a undergoes facile fluoride ion loss in a reaction with water, giving [Ir 2 (CH 3 )(κ 1 ‐CHCF 2 )(CO) 2 (μ‐OH)(dppm) 2 ][OTf]. Carbon–fluorine bond activation by water is well documented,3f, 6d, 9a, 25 and Hughes and co‐workers have shown that the coordination of water can increase its acidity sufficiently to allow it to protonate an α‐fluorine atom,3f, 6d, 25 leading to its loss as HF. Consequently, we sought to determine whether water‐promoted CF activation could also occur for the C 2 F 4 ‐ and 1,1‐C 2 F 2 H 2 ‐bridged complexes ( 2 , 6 a or 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 1,1‐difluoroethylene has received much less attention, and to our knowledge, only two examples involving its CF bond activation are known, apart from our own preliminary report 9d. The first example demonstrates that [RhCl(PPh 3 ) 3 ] and other related Rh I complexes react with 1,1‐difluoroethylene under hydrolysis conditions to form the carbonyl complex [RhCl(CO)(PPh 3 ) 2 ], in which the carbonyl carbon originates from the difluoroethylene ligand 9a. More recently, Jones and co‐workers have accomplished the hydrodefluorination of 1,1‐difluoroethylene by [Cp* 2 ZrH 2 ] (Cp*=pentamethylcyclopentadienyl), producing two equivalents of [Cp* 2 ZrHF], along with the formation of [Cp* 2 Zr(Et)H], the result of the hydrodefluorinated product, ethylene, being trapped by [Cp* 2 ZrH 2 ] 7c.…”
Section: Introductionmentioning
confidence: 98%
“…Complexes involving a range of metals from across the periodic table have shown a propensity to activate carbon−fluorine bonds, and although significant successes have been achieved in the activation of fluorinated aryl systems, including catalytic hydrodefluorination of perfluorobenzene, surprisingly little has been reported on the transition-metal-promoted activation of fluorine-containing olefins. The main focus involving fluoroolefin activation has involved hydrodefluorination, a process in which a C−F bond is replaced by a C−H bond. However, the main objective of this reaction has been to replace as many C−F bonds as possible with C−H bonds, and as such, selectivity has not been the main focus. In fact, only a few examples of selective C−F bond activation of fluoroolefins have been reported, ,, and of those, the selectivity observed has mainly differentiated between C−F bonds involving sp 2 - and sp 3 -hybridized carbons. ,, Braun and co-workers have shown that [HRh(PEt 3 ) 3 ] can exclusively activate the sp 2 -hybridized bonds of hexafluoropropene, leaving all sp 3 -hybridized C−F bonds untouched, which in the presence of hydrogen gas yields 1,1,1-trifluoropropane .…”
Section: Introductionmentioning
confidence: 99%
“… 22 Similarly, Kemmitt and co-workers have reported that carbonylrhodium complexes reacted differently with fluoroolefins depending on whether the reaction was taking place in a steel autoclave or in regular laboratory glass vessels. 23 Cairns et al reported spontaneous reactions with glass NMR tubes when trying to characterize fluorocomplexes of platinum, resulting in observation of NMR-resonances that are characteristic for silicon fluorides formed as a consequence of HF reacting with the glass surface. 24 Related decomposition and reaction with glass vessels when handling fluorinated metal complexes has since been reported by Atherton 25 and Gil-Rubio.…”
Section: Container-dependent Stability Of Organofluorine Compoundsmentioning
confidence: 99%